Pos-processador para modelos bidimensionais nao-lineares do metodo dos elementos finitos - Samuel Silva Penna (2007)
This masters thesis presents a post-processor program for two dimensional Finite Element Method models. The program can represent linear and nonlinear models through graphics interactive resources. The program makes use of an adjacency structure based on half-edges to manipulate the geometrical information and the data of the models, as well to allow the post-processor generalization. The representation of results by isoranges of values uses domain subdivision techniques, based on Delaunays triangulation and on the models mesh. Techniques for results extrapolation and smoothness are available.The implementation, according to the object-oriented programming paradigm, uses the JAVA programming language and several APIs (Application Program Interface) and graphical packages available in this language. Through the use of various technological solutions for software development, the implementation takes place with the progressive rearrangement and extension of the INSANE (INteractive Structural ANalysis Environment) system resources, a segmented and friendly to change computational environment . The system applicationsorganization, as well all design patterns used, are present, and the post-processors object-oriented design is, then, detailed. Several examples are used to demonstrate the functionalities and main features of the program.